Analysis of Mustahik Welfare Improvement Strategy Through MSME Utilization Program by LAZISMU Medan City - Nasution, Uslaini Rahma; Edi, Sarwo (Universitas Muhammadiyah Sumatera Utara, 2022)
LAZISMU Medan has several programs in an effort to empower the people's economy, LAZISMU distributes productive zakat to improve the welfare of mustahikthat isthrough the MSME Utilization program which has the main task of providing capital to business actors. Problems when running the MSME empowerment program include zakat funds that are not on target and the businesses run by mustahik are not all running smoothly. This study aims to determine the MSME Utilization system and the strategies implemented by LAZISMU Medan City, as well as to find out the cause of the business run by mustahik not running smoothly. This research method uses qualitative research methods, with data collection from interviews, observations and documentation to determine the LAZISMU system and strategy in Medan City and to find out the causes of Mustahik's business not prospering. There are 5 informants in this research. The results of the research carried out can be seen that the empowerment of MSMEs using the offense and application system has a very big influence on the welfare of the community and can alleviate poverty in the city of Medan, the strategy used by LAZISMU Medan City of the four strategies is only one that is realized and one that is not realized, namely Training Entrepreneurship.